The wrong kind of bark - Donaldson, Julia; Parsons, Garry (London : Egmont UK, 2004)
A daydreaming student misunderstands a nature study homework assignment, with humorous results.
2.7
K-3
Keywords: Nature study -- Juvenile fiction; Schools -- Juvenile fiction; Nature study -- Fiction; Schools -- Fiction; Nature study -- Fiction; School stories; Readers (Elementary).